Public Education and Social Reconstruction in Bosnia and Herzegovina and Croatia - Freedman, Sarah; Čorkalo Biruški, Dinka; Levy, Naomi; Abazović, Dino; Leebaw, Bronwen; Ajduković, Dean; Đipa, Dino; Weinstein, Harvey (2004)
In 2000 we launched a series of studies to try to understand what role, if any, publc education could play in social reconstruction in Croatia and BiH. We had two questions: what do communities think about the role schools could play in creating a memory of the past through curriculum? And, second, how do they want the schools organized to deliver that curriculum? Over the course of three years we collected the views of parents, teachers, students and administrators in two of the most ethnically divided cities of the former Yugoslavia – Vukovar and Mostar – on a wide range of issues, including interethnic relations in schools, the teaching of history, school integration, curricula development, and national identity. The surveys centered on the sixth and eighth grades of elementary school and the second year of secondary school, while interviews and focus groups centered on the second year of secondary school. Our study shows that in order to make progress with respect to social reconstruction and resolving dilemmas about the schools in Vukovar and Mostar, the conflicting groups need to reach a consensus through public debate. In case of Vukovar it means reaching a consensus about what kind of schooling would allow preservation of minority culture and in the same time provide an integrative and safe environment for children to interact, learn and socialize with their peers from other group. In case of Mostar it means a timely fashion of school and classroom integration. While Bosniaks are ready for integration, Croat youth are neutral on this issue. This is why the work must be done with the Croat community to help its members feel secure about fostering a Croat national identity outside of school as well as in integrated schools and classrooms.
Projekt MZOS
ENG